(untitled) (Eurasian Scientific Herald, 2026)
Tumor necrosis factor-alpha (TNF-alpha) is a multifunctional proinflammatory cytokine implicated in the chronic inflammation that drives venous wall remodeling and trophic complications in chronic venous insufficiency (CVI). The functional promoter polymorphism G308A (rs1800629) may modify susceptibility to the disease and its complicated forms.